Determinants of economic practices among elderly urban migrants in Khon Kaen, Thailand - Thongsrikate, Ittipong; Ayuwat, Dusadee; Chaytaweep, Saowalak (Kasetsart Journal of Social Sciences, 2021)
This article aims to study the determinants of economic practices among elders who have migrated to Khon Kaen city, a city of economic importance in northeast Thailand. The study applied quantitative research methodology with data analysis at the level of individual units. Data were collected in April 2018 from interviews of 276 elderly migrants aged over 60 years old. Data analysis incorporated descriptive statistics and multiple regression analysis. The findings showed that determinants of economic practices among elderly urban migrants in Khon Kaen, Thailand included household roles, positive health care behavior, daily life activities, preparations taken prior to migration, and the location of the migrant’s origin was a statistical significance of .01 The length of time the migrant had lived in the new destination was a statistical significance of .05. All of the aforementioned factors were able to predict economic practices among elderly urban migrants in Khon Kaen, Thailand at 62.6 percent. Therefore, social and environmental factors, as well as factors related to migrant planning, are important determinants of economic practices among elderly migrants.